Penerapan Teknik Steganografi dalam Gambar pada Aplikasi Telegram Menggunakan Metode Least Significant Bit (LSB) - Lu’lu’ Atik Fitriyani; Fahmi Fachri (Jurnal Teknologi Informasi dan Multimedia, 2026)
In the digital era, the threat of data leakage demands secure information exchange mechanisms on instant messaging applications. This study aims to implement and test the robustness of the Least Significant Bit (LSB) steganography method on image media transmitted through the Telegram platform to ensure information confidentiality and create secure cyber communication against eavesdropping. The novelty of this research lies in the comparative analysis of the pure LSB method's robustness against Telegram's compression protocols, which frequently corrupt lower bits in digital media. This study employs an experimental quantitative approach by testing 15 digital image samples in PNG, BMP, and JPG formats sourced from the Google public repository. The experimental process involves embedding text messages using StegOnline tools, transmission via Telegram, extraction, and image quality analysis based on Mean Squared Error (MSE) and Peak Signal-to-Noise Ratio (PSNR) metrics. The test results indicate that the LSB method achieves a 100% extraction success rate and a Bit Error Rate (BER) of 0 when utilizing the "send document" feature due to its lossless transmission nature, with optimal visual quality indicated by PSNR values above 58 dB. Conversely, transmission through the "send image" feature causes extraction failure due to the platform's compression that corrupts the secret bits. This study concludes that the accuracy stability of LSB steganography highly depends on selecting a lossless transmission for-mat to fully guarantee data integrity.